Novel poly(alkyd-urethane)s from vegetable oils: synthesis and properties - Ling, Jem Shan; Mohammed, Issam Ahmed; Gazalli, Arniza; Khairuddean, Melati (Elsevier, 2014)
Triglycerides of palm (Elaeis guineensis) oil, soy (Glycine max) oil and sunflower (Helianthus annuus) oil were converted to monoglycerides by glycerolysis process. The monoglycerides derived from the different oils were reacted with phthalic anhydride at 2:1 monoglyceride-to-phthalic anhydride ratio to obtain novel polyols called alkyd diols. The polyols were reacted with 4,4′-methylenediphenyldiisocyanate (MDI) to produce five novel poly(alkyd-urethane)s (PAU), namely palm oil based poly(alkyd-urethane) (POPAU), soy oil based poly(alkyd-urethane) (SOPAU), sunflower oil based poly(alkyd-urethane) (SFPAU), palm-soy oils based poly(alkyd-urethane) (POSOPAU) and palm-sunflower oils based poly(alkyd-urethane) (POSFPAU). The successful synthesis of the monoglycerides, alkyd diols and poly(alkyd-urethane)s were confirmed by FTIR, 1H NMR, 13C NMR spectroscopy and their morphology were evaluated by scanning electron microscopy (SEM). Further analyses included viscosity, solubility, iodine number testing, gel content, drying time test, thermogravimetric analysis (TGA), crosshatch adhesion tests, impact strength, pencil hardness, chemical and water resistance. Palm oil poly(alkyd-urethane) showed good thermal stability with only 5% weight loss temperature in nitrogen at 270 °C. Improvements in coating performance after blending with sunflower oil or soy oil based alkyd-diols were also observed.